ABUNDANCE AND DISTRIBUTION OF ANOPHELES MOSQUITO IN RELATION TO PHYSICOCHEMICAL PROPERTIES IN DELTA STATE, NIGERIA - Ojianwuna, C. C.; Enwemiwe, Victor; Ekeazu, C. N. (FUDMA JOURNAL OF SCIENCES, 2021)
In this study, the effect of physicochemical parameters as determinants for the abundance and distribution of Anopheles mosquitoes was examined. Physicochemical variables such as pH, temperature, DO, TDS, flow velocity, salinity and electrical conductivity were determined using standard procedures. Three communities in Ukwani LGA, Delta State were mapped out and sampled. Immature stages of Anopheles mosquitoes were collected from potential breeding sites using 350 ml dip ladles and scooping spoon. The physicochemical parameters showed that air, and water temperature, pH, and dissolved oxygen were higher in Umutu compared to the other sampled communities (Obiaruku and Umukwata). Salinity, conductivity, total dissolved solids and flow velocity were higher in Obiaruku and Umukwata compared to Umutu. Various levels of significance (p <0.05) were recorded within sampled months and communities. The density of Anopheles mosquitoes were higher in ponds and puddles (42.1 and 32.6%) in Obiaruku compared to other locations irrespective of the sampled months. Highest density was also recorded in the month of September (42.3%) compared to other sampled months. Temperature, pH, DO, TDS and conductivity were in acceptable limits for mosquito survival. All parameters were positively correlated with the density of Anopheles mosquitoes. Thus, in practical terms for vector control, this study has demonstrated the importance of considering these physicochemical parameters when manipulating mosquito breeding sites for mosquito control programs, discourage their proliferation and decline the malaria burdens